Preclinical pharmacokinetics and metabolism of a novel prototype DNA-PK inhibitor NU7026 - Nutley, B P; Smith, N F; Hayes, A; Kelland, L R; Brunton, L; Golding, B T; Smith, G C M; Martin, N M B; Workman, P; Raynaud, F I (British journal of cancer, 2005)
In this study we investigated the in vitro time dependence of radiosensitisation, pharmacokinetics and metabolism of NU7026, a novel inhibitor of the DNA repair enzyme DNA-dependent protein kinase (DNA-PK). At a dose of 10 μ M , which is nontoxic to cells per se , a minimum NU7026 exposure of 4 h in combination with 3 Gy radiation is required for a significant radiosensitisation effect in CH1 human ovarian cancer cells. Following intravenous administration to mice at 5 mg kg −1 , NU7026 underwent rapid plasma clearance (0.108 l h −1 ) and this was largely attributed to extensive metabolism. Bioavailability following interperitoneal (i.p.) and p.o. administration at 20 mg kg −1 was 20 and 15%, respectively. Investigation of NU7026 metabolism profiles in plasma and urine indicated that the compound undergoes multiple hydroxylations. A glucuronide conjugate of a bis-hydroxylated metabolite represented the major excretion product in urine. Identification of the major oxidation site as C-2 of the morpholine ring was confirmed by the fact that the plasma clearance of NU7107 (an analogue of NU7026 methylated at C-2 and C-6 of the morpholine ring) was four-fold slower than that of NU7026. The pharmacokinetic simulations performed predict that NU7026 will have to be administered four times per day at 100 mg kg −1 i.p. in order to obtain the drug exposure required for radiosensitisation.